Determination Of Zn Species Using Ultrafiltration And Different Solid Sorbents. - Suitchatit, Charuwan; Mohamed, Norita; Lim, Poh Eng; Sirinawin, Warapon (2004)
A method for the determination of operationally-defined metal species at natural concentration levels has been developed. The method is based on a combination of physical characterization by size fractionation using ultrafiltration and chemical characterization by retention studies on different solid sorbents.